REDUCING WASTE ON MACHINE FABRICATION A MIXER COOKIE DOUGH USING LEAN MANUFACTURING AT PT MEKANIK SINERGI BERSAMA (International Journal of Psychosocial Rehabilitation, 2020)
As through technology, business development manufacturing had such intense competition. To win the competition, company use many ways, including optimizing resources, excellent human resources, process production to product quality will improve. Talking about produce, need to contribute to the process of producing full to productive activities on added value and try to avoid or limiting idle/delay, wait, extravagance, and so on. The company which is the place of research for this journal is PT Mekanik Sinergi Bersama (PT MSB) is an incubator company engaged in manufacturing. The problem that arises at PT Mekanik Sinergi Bersama is the lateness in the work of the cake dough mixer machine due to the large amount of waste contained in the process. After finishing the manufacturing process of the first machine, the company will reproduce the cake dough mixer machine. This study based on existing problems will evaluate the process of machining so that it can reduce the waste that exists on the production floor using the concept of lean manufacturing. The concept of lean manufacturing used to minimize waste that occurs on the production floor. To reduce waste that occurs, the activity mapping process (PAM) is one of the specific mapping tools. From the results of an improved analysis of recommendations, the lead time is reduced by 4 hours 55 minutes. From the analysis using PAM, there is a reduction in NVA activity from 4% to 1%.